Pengaruh Likuiditas, Solvabilitas dan Aktivitas Terhadap Profitabilitas: Bukti Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Hendi Rohendi; Sudradjat Sudradjat (Indonesian Accounting Literacy Journal, 2021)
This study aims to determine the effect of Liquidity, Solvency and Activity on Profitability of Property and Real Estate Companies Listed on the IDX either simultaneously or partially. The research method used in this research is quantitative with data collection techniques through financial statement documentation, then analyzed using multiple linear regression. The population in this study are Property and Real Estate Companies listed on the IDX for the period 2014-2017 with a sample of 24 companies. The results of the study show that (1) simultaneously Liquidity, Solvency and Activity have a positive and significant effect of 39.1% on Profitability in Property and Real Estate Companies Listed on the IDX. (2) Partially, Liquidity has a positive but not significant effect on Profitability, Solvency has a negative but not significant effect on Profitability, and Activities have a positive and significant effect on Profitability in Property and Real Estate Companies Listed on the IDX.